2011
DOI: 10.1097/ta.0b013e3181fef5eb
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Complex Trauma of the Foot

Abstract: Early outcome after complex trauma of the foot was essentially determined by soft tissue injury, whereas long-term outcome was determined more by the trauma of the bones and joints. Objective measurements such as dynamic pedography helped to better understand patients' limitations. Orthotic supply could be improved in a reasonable number of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
16
0
5
Order By: Relevance
“…In the LEAP study subgroup analysis of 174 severe open foot injuries, there were significantly worse SIP values after limb preservation versus lower leg amputation when flap coverage and/or ankle arthrodesis were necessary [21]. In an analysis of 50 complex foot injuries, Kinner et al (2011) reported a significant correlation between amputation and ISS [ 16 as well as the primary soft tissue damage [39]. In contrast to the vascular surgery principle of waiting for demarcation of hypoperfused limb areas, in acute trauma, an early decision regarding the need for eventual amputation is advisable to enable early definitive soft-tissue closure [101,102].…”
Section: Explanationmentioning
confidence: 99%
“…In the LEAP study subgroup analysis of 174 severe open foot injuries, there were significantly worse SIP values after limb preservation versus lower leg amputation when flap coverage and/or ankle arthrodesis were necessary [21]. In an analysis of 50 complex foot injuries, Kinner et al (2011) reported a significant correlation between amputation and ISS [ 16 as well as the primary soft tissue damage [39]. In contrast to the vascular surgery principle of waiting for demarcation of hypoperfused limb areas, in acute trauma, an early decision regarding the need for eventual amputation is advisable to enable early definitive soft-tissue closure [101,102].…”
Section: Explanationmentioning
confidence: 99%
“…Arthough extensive fasciotomy in a severely injured foot has the potential for complications like wound healing problems, infection, and extensive scarring, most clincal series on fasciotomy for FCS do not report any complications directly related to compartment syndrom release [8,17,27,31], in one series of 14 fasciotomies one skin necrosis occurred and one free flap coverage was needed [29]. On the other hand, multiple late complications have been described for untreated compartment syndrome, as outlined below.…”
Section: Aftercarementioning
confidence: 97%
“…Recent studies on complex trauma of the foot revealed residual toe deformities in about two thirds of cases with presumably overlooked FCS and even despite early fasciotomy [17].…”
Section: Late Reconstruction In the Presence Of Subsequent Deformitymentioning
confidence: 99%
See 1 more Smart Citation
“…B. Avulsions verletzungen) primär durch das Weich teilmanagement und sekundär durch den Behandlungserfolg der knöchernen und ligamentären Verletzungen determiniert [4].…”
unclassified